Answer:
a= 4
b= -1
c= 10
Explanation:
First we start by multiplying both sides of 1/2c = 5 by 2.
c = 10
Add b to both sides of the last equation to make it a=b+5
knowing these two things, we can plug them into the first equation like this:
2(b+5) + b + 10 = 17
then you solve for b:
distribute the 2
2b + 10 + b + 10 = 17
combine like terms
3b + 20 = 17
subtract 20 from each side
3b = -3
divide by 3
b = -1
then you can plug that into the last equation again so a - (-1) =5
Subtracting a negative is the same as adding so its a + 1 = 5 or a = 4